PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN LEMBAGA SOSIAL YAYASAN INSPIRASI ANAK BANGSA - Rizal Rahmawan; Choiriawati Choiriawato; Syaifuddin Syaifuddin (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
Good work environment (good facilities and infrastructure) or bad (less spacious workspace, uncomfortable waiting room for customers because it can disrupt concentration in an organization). The comfort of the employee's work environment can trigger employees to work better so that employee performance can be achieved optimally. (2) The influence of the work environment on employee performance at the Inspirasi Anak Bangsa Foundation Social Institution. The work environment can be interpreted as the entire tooling faced, the surrounding environment in which a person works, the method of work, as the influence of his work both as individuals and as a group. The hypothesis in this study "It is suspected that there is a significant influence of the environment on the marketing of business/products of the Inspirasi Anak Bangsa Foundation Social Institution. The place in this research is at the Social Institution of the Inspirasi Anak Bangsa Foundation, which is located at YIAB Mulia Center Jl. Block Highway Bullet Warehouse. H.190. Tebet, Jakarta 12830. The population and sample are 40 people. The data analysis technique used is validity test and reliability test, linearity test, regression test, and t . test The working environment conditions that occur at the Inspirasi Anak Bangsa Foundation Social Institution include the working atmosphere Relationships with colleagues The availability of work facilities is well reflected. The work environment has a significant effect on employee performance. This shows that the good and bad working environment cannot be separated from all the elements involved in creating a work environment regarding physical facilities, room arrangement, organization or agency location and working atmosphere within an agency.